Analisis Dakwah Multikuktural KH. Ahmad Mustofa Bisri Rembang (Konsep dan Metode Dakwah) - Muhamad Bisri Mustofa (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2020)
Multiculturalism or what is often referred to as cultural diversity is one of the hegemony possessed by the Indonesian nation. However, there are still forms of movement carried out by a religious community to create diversity both in religion and in society, this has resulted in terms of intolerance developing and leading to extremism to replace the ideology of the Unitary State of the Republic of Indonesia (NKRI). KH Ahmad Mustofa Bisri's multicultural da'wah in the midst of diversity in society, where diversity can give birth to a moredat (balanced) attitude, is fair and chooses to be wise and wise towards something or what is often called moderation (middle attitude). KH Ahmad Mustofa Bisri's approach and method of preaching is a process of social interaction in order to spread Islamic teachings that are rahmatal lil alamin to be implemented in social, cultural and religious life in Indonesia. KH Ahmad Mustofa Bisri (Gus Mus) 's concept and view on multiculturalism strongly recognizes and respects the existence of various cultures and different religions. The multicultural da'wah carried out by KH Ahmad Mustofa Bisri is a mission to create peace and comfort in the midst of Indonesian people with different ethnic, racial, religious, ethnic and cultural backgrounds. Analysis The results of this study are the multicultural da'wah concept and the multicultural da'wah method carried out by KH. Ahmad Mustofa Bisri is through preaching media such as (1) The method of preaching bi al-kalam such as his writings on Facebook, Twitter, books, Springs Websites, paintings and poetry (2) Methods of da'wah bi alkalam / bi al-oral such as lectures - Gus Mus's lectures can be viewed through the YouTube channel, (3) Biological method, this can be seen from the personality of Gus Mus, who is very simple and soothing so that he can be accepted in the midst of a diverse society. The multicultural da'wah carried out by KH. Ahmad Mustofa Bisri has two models, namely (1) a cultural approach as a solution for the community to always live in harmony and side by side between religious communities. (2) A social approach as an effort to solve humanitarian problems together.